Osteoporosis Prevention Exercise Effects to Bone Density in Children with Thalassemia - Andreas Arie Widiadiaksa Waluyojati; Marietta Shanti Prananta; Marina Annette Moeliono (International Journal of Integrated Health Sciences, 2018)
Objective: To discover recommendation of osteoporosis prevention exercise (OPE) for children with thalassemia.Methods: This study was conducted in the period of April–June 2017 by using quasi experimental and pretest-posttest designs. Eleven thalassemia patients who were the members of a thalassemia patient foundation and an association of parents of thalassemia patients, Yayasan Thalassaemia Indonesia and Perhimpunan Orangtua Penderita Thalassemia Indonesia, were enrolled in the study as the subjects. Sample calculation was carried out by using consecutive sampling method. The subjects were given OPE intervention 2 times per week during 12 weeks with 35 minutes of each session. BMD of spinal lumbar examination was performed before and after practicing OPE. Collected data were analyzed statistically by using paired t and Wilcoxon tests with p value <0.05.Results: After the intervention, BMD value of L1, L2, and L3 segments did not improve significantly while BMD value of L4 segment and average Z-score showed significant improvement (p<0.05).Conclusions: Osteoporosis prevention exercise can improve BMD in children with thalassemia. Continuous OPE program can be recommended for children with osteoporosis-induced thalassemia.Keywords: Bone mineral density, osteoporosis, osteoporosis prevention exercise, thalassemia, Z-score DOI: 10.15850/ijihs.v6n2.1349